Warmer temperature accelerates reproductive senescence in mosquitoes - Lindsay E. Martin; Tania Y. Estévez-Lao; Tobias C. McCabe; Julián F. Hillyer (Frontiers in Physiology)
To reproduce, most female mosquitoes must ingest blood to obtain nutrients for viable eggs. Global warming is increasing mosquito body temperature and hampering their reproduction. Moreover, because it takes several days to produce eggs and mosquitoes are short-lived, the age of blood feeding determines whether reproduction is feasible. Given that warmer temperature and aging both impair reproduction, we scrutinized whether temperature modifies the aging-based decline in fecundity and fertility. By rearing the African malaria mosquito, Anopheles gambiae, at three temperatures and offering them a blood meal at four ages, we demonstrate that warmer temperature reduces blood feeding propensity and blood meal mass. Warmer temperature and aging decrease survival, delay oviposition, and reduce oviposition success, fecundity, and fertility. Importantly, warmer temperature quickens the onset of the aging-dependent decline in fecundity and fertility, and at the warmest temperature of 32°C, mosquitoes are infertile. Warmer temperature accelerates reproductive senescence, which has implications for disease transmission in this warming world.